A retrospective study of condyloma acuminata profile in outpatient clinic of dermato-venereology Sanglah General Hospital Denpasar, Bali-Indonesia period 2015-2017 - Ni Made Dwi Puspawati; Sissy; Dewi Gotama (Explorer Front, 2018)
Introduction: Condylomata acuminata (CA) is human papillomavirus (HPV) infection, and one of the most common sexually transmitted disease, characterized with papul or papillomatous nodule in genital, perineum and anal, this disease can be asymptomatic as well. Some study proved sexually transmitted infection increases the incidence of Human immunodeficiency virus (HIV)/ acquired immunodeficiency syndrome (AIDS), and vice versa. Management of CA is Trichloroacetic acid (TCA), Tincture Podophyllin, and Electrocautery. This study aims to determine profile of condyloma acuminata in Dermatovenereology Outpatient Polyclinic Sanglah General Hospital Denpasar Bali period 2015-2017. A retrospective study during three years (2015-2017). Method: Data was obtained from medical record in Dermatovenereology Outpatient Polyclinic Sanglah General Hospital Denpasar Bali period 2015- 2017. Result: Total patient condyloma acuminata is 260 patients (5.48%), male is dominant 70 patients (67.31%), range age 12-35 years old (123%), there was 59 patient who infected with HIV (22.31%), with five pregnancy (1.92%). Most therapy is given trichloroacetic acid (TCA) (79.62%). Conclusion: Men suffered from condyloma acuminata more commonly than women, the most common treatment for this condition is trichloroacetic acid (TCA)